Effectiveness of Iron Electrode Pairs Electrocoagulation on Total Suspended Solid Removal in Coal Mine Water with a Continuous Flow Reactor - Zamani, Syarif Makki; Syafila, Mindriany; Abfertiawan, Muhammad Sonny (Jurnal Teknik Lingkungan, 2023)
Indonesia is a country with large potential for energy and mineral resources, including coal. Coal mine water is characterized by high levels of total dissolved solids (TSS). This occurs when overburden excavation activities are carried out so that clay minerals are exposed. Rainwater at a certain volume contacts the minerals contained in the overburden and flows on the surface carrying solid material and oxidation products. This study aims to determine the effect of current strength and detention time on electrocoagulation performance in removing TSS levels. The configuration of the electrocoagulation study is to use a pair of monopolar iron electrodes with a continuous operation method. This study used artificial waste with a TSS content of 3865 mg/L. The variations used in this study were current strength (2 A; 4 A; and 6 A) and detention time (15 minutes; 30 minutes; and 45 minutes). The results showed that the electrocoagulation process was able to eliminate TSS levels. The optimum condition for TSS removal in this study was achieved at a current strength of 4 A and a detention time of 30 minutes with a TSS removal percentage of 98,64% from the initial TSS concentration of 3865 mg/L to 52,43 mg/L. The TSS content has met the quality standards of East Kalimantan Provincial Regulation Number 02 of 2011 concerning Management of Water Quality and Control of Water Pollution in the TSS parameter.